Spain overseas - Moses, Bernard, 1846-1930. (New York, Printed by order of the trustees, 1929)
"The following chapters are ... marginal comments on some sections of the general history of Spanish America" -- Preface.
"Reference": page 109.
Also issued online.
NLJCols20082021
Keywords: Latin America -- Civilization; Spain -- Civilization; Spain -- Colonies -- Administration; Spain -- Colonies -- America; Philippines -- Politics and government -- 1898-1935.; Civilization; Colonies -- Administration; Politics and government; Spanish colonies; America; Latin America; Philippines; Spain; 1898-1935